PENGARUH BUDAYA BISNIS MASYARAKAT DAN LITERASI KEUANGAN TERHADAP MINAT BERWIRAUSAHA MASYARAKAT DI KOTA YOGYAKARTA - Fredericha Seran; Sri Lestari Yuli Prastyatini (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2022)
The purpose of this study was to determine the effect of Community Business Culture (XI), Financial Literacy (X2), Social Media Development (X3), and Entrepreneurial Creativity (X4) on Entrepreneurial Interest (Y) in Yogyakarta City. This type of research is quantitative research. The population in this study are people who are entrepreneurs in the city of Yogyakarta with a sample of 40 people. The data collection technique used is a survey method using a questionnaire. Then the data is processed using SPSS IBM Version 25, the data analysis techniques used are data analysis test, data quality test, classical assumption test, multiple regression test, t test, f test and coefficient of determination. Based on the results of this study, Community Business Culture has a positive and significant effect on the interest in Entrepreneurship. This is evidenced by the t-count value of 2.651 and a significance value of 0.012 <0.05. Financial Literacy has a positive and significant effect on interest in entrepreneurship, this is evidenced by the t-count value of 3.142 and a significant value indicated by 0.003 <0.05. The development of social media has a positive and significant effect on interest in entrepreneurship, this is evidenced by the t-count value of 2.473 and a significant value indicated by 0.018 <0.05. Entrepreneurial creativity has a positive and significant effect on interest in entrepreneurship, this is evidenced by the t-count value of 2.636 and a significant value indicated by 0.012 <0.05..